1992
DOI: 10.1161/01.cir.85.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain measures of heart period variability and mortality after myocardial infarction.

Abstract: Background. We studied 715 patients 2 weeks after myocardial infarction to establish the associations between six frequency domain measures of heart period variability (HPV) and mortality during 4 years of follow-up.Methods and Results. Each measure of HPV had a significant and at least moderately strong univariate association with all-cause mortality, cardiac death, and arrhythmic death. Power in the lower-frequency bands -ultra low frequency (ULF) and very low frequency (VLF) powerhad stronger associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
769
5
32

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,501 publications
(837 citation statements)
references
References 23 publications
31
769
5
32
Order By: Relevance
“…Reduced power in the very low frequency band has been shown to have a stronger association with all-cause mortality than the low frequency and high frequency bands. In addition, low power in the very low frequency band has been shown to be associated with arrhythmically mediated death (Bigger et al 1992). …”
Section: Very Low Frequency Powermentioning
confidence: 99%
“…Reduced power in the very low frequency band has been shown to have a stronger association with all-cause mortality than the low frequency and high frequency bands. In addition, low power in the very low frequency band has been shown to be associated with arrhythmically mediated death (Bigger et al 1992). …”
Section: Very Low Frequency Powermentioning
confidence: 99%
“…13 The clinical importance of HRV became apparent in the late 1980s when HRV was confirmed to be a strong, independent predictor of mortality following acute myocardial infarction. [14][15][16] Most investigators have suggested that HF and RMSSD are predominantly a response to changes in parasympathetic tone, whereas LF and SDNN are dually influenced by cholinergic and adrenergic activities, as well as by other physiological inputs. The values of TP are similar to those of SDNN; they affect control of the autonomic nervous system.…”
Section: Analysis Of Time Domain and Frequency Domain Ofmentioning
confidence: 99%
“…Besides their application in the assessment of cardiovascular autonomic function in diabetic patients, HRV and BRS are used in cardiology for risk stratification after myocardial infarction. Low HRV is associated with mortality risk in post-myocardial infarction patients [23,24] and also in the general population [25,26]. Also, autonomic neuropathy has been proposed to play a role in the aetiology of cardiovascular disease [27,28,29,30,31] and nephropathy [32,33] in diabetes.…”
mentioning
confidence: 99%